1999
DOI: 10.1076/opep.6.3.181.1502
|View full text |Cite
|
Sign up to set email alerts
|

The VECAT Study: Methodology and statistical power for measurement of age-related macular features

Abstract: The VECAT study methodology appears to be highly reliable and to have sufficient power to detect the differences in the four-year progression of soft distinct and indistinct drusen and pigment abnormalities between the treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…The same grader was involved in the photo grading of photographs in the two baseline examinations (VIP and VECAT studies), as well as in the grading of follow‐up examinations. The intragrader reliability was calculated in the VECAT study and was found to be high (kappa 0.6−1.0) 30 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The same grader was involved in the photo grading of photographs in the two baseline examinations (VIP and VECAT studies), as well as in the grading of follow‐up examinations. The intragrader reliability was calculated in the VECAT study and was found to be high (kappa 0.6−1.0) 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on the assessment of retinal photographs, progression of early AMD signified that lesions present at baseline (1992−1995) had worsened at the CHARM examination (2001). A detailed description of the diagnostic criteria used to define AMD progression (based on photo grading) has been described previously 30 . In short, progression of drusen represented the stepped increase of six possible features: size (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the grading procedures are presented elsewhere. 26,27 Slit lamp examination Following ophthalmic photography, the clinical slit lamp eye examination was conducted. Pterygium and corneal opacities in the optical zone were recorded and graded in millimeters (pterygium) and degree of transparency (corneal opacity), as they could affect the quality of macular photography and subsequently the grading assessment.…”
Section: Ophthalmic Examinationmentioning
confidence: 99%
“…13 Details of the grading procedures are presented elsewhere. 14,15 In brief, following the specifications outlined by the International group, a grid consisting of three circles concentric with the centre of the macula that represent, respectively, the central, middle, and outer subfields was used to assist with the grading of early and late AMD lesions. The central, middle, and outer circles have diameters of 1000, 3000, and 6000 mm, respectively.…”
Section: Assessment Of Amd On Macula Photographsmentioning
confidence: 99%